The EU's Multi-Annual Financial Framework for 2014-2020: an Old Construct Fit for a Changed EU? - Sándor Richter (FIW - Research Centre International Economics, 2013)
As a consequence of the 2008-2009 international financial crisis the European Union is undergoing per-haps its most difficult period since the beginnings of the European integration. The response to this challenge includes decisions and planned steps to strengthen fiscal discipline in the member states, safeguard measures against a falling-apart of the eurozone and the introduction of a Union-wide super-vision of the European banking sector. A new fiscal capacity (budget) for the eurozone is under consid-eration. It seems that the extraordinary situation has triggered a wave of extraordinary reforms throughout the EU. In one area, the Community Budget, however, time seems to have stopped temporarily. The European Council of 22-23 November 2012 was unable to arrive at a compromise on the terms of the Multi-annual Financial Framework (MFF or the EU budget) and postponed the decision to 7-8 February. The contradiction between the decades-old unsolved budgetary problems and the rapidly changing environment cannot be greater as it is now.
Keywords: F36; 330; European Union; Multiannual Financial Framework; EU budget; net financial position; Cohesion Policy; CAP; Europe 2020